Fostering Prospective Teachers’ Disposition: A Lesson Study in Linear Programming Topics Embedded by Technology - Krisnadi, Elang; Kandaga, Thesa (Polyhedron International Journal in Mathematics Education, 2024)
In modern education, especially in higher degree programs, disposition was one of several factors that highly affected the learning process. The purpose of this research was to foster mathematical disposition among prospective teachers through a technology approach. POM-QM represented technology embedded into the learning process. Each cycle started with planning the embedding of technology into learning, realizing the plan by engaging a model teacher and an observer, and then ending with reflection to improve the next learning process to be applied to another class or the next topic. This lesson study began at the very beginning of linear programming. The conclusion was that the chapter design was able to foster mathematical dispositions. Some other affective and cognitive skills were known to have improved. The conclusion also covered some other unwritten but proper actions to take in the learning process based on lesson study reflection and evaluation. It was hoped that subsequent researchers would be able to implement lesson study activities during lecture activities.